Promoting entrepreneurship among informatics engineering students: insights from a case study. (2nd January 2017) - Fernandes, João M.; Afonso, Paulo; Fonte, Victor; Alves, Victor; Ribeiro, António Nestor
ABSTRACT: Universities seek to promote entrepreneurship through effective education approaches, which need to be in permanent evolution. Nevertheless, the literature in entrepreneurship education lacks empirical evidence. This article discusses relevant issues related to promoting entrepreneurship in the software field, based on the experience of a 15-European Credit Transfer and Accumulation System course. This course seeks to instil in the students the recognition of the need to reconcile technical and business visions, organisational and commercial aspects, most of which have never been addressed previously. A series of semi-structured interviews made it possible to obtain relevant insights about the teaching–learning process underlying this course and its evolution over a seven-year period. Materials related with this course have been analysed, namely guidelines produced by the teachers and deliverables produced by the students. This article discusses the dimensions that were identified as fundamental for promoting entrepreneurship skills in the field of software, namely teamwork, project engagement, and contact with the market.